PENGARUH PERCEIVED ATTRACTIVENESS OF NOSTALGIC APPEALS DAN PERCEIVED COLLECTIVE NOSTALGIA TERHADAP PURCHASE INTENTION PADA PRODUK KOLABORASI EDISI NOSTALGIA CHIKI BALLS X RANGGA & CINTA: THE REBIRTH OF AADC - Yonna Chantika Novyanasari; Muhammad Bayu Widagdo (Interaksi Online, 2026)
Chiki, a snack brand under PT Indofood CBP Sukses Makmur Tbk, faces intense competition in Indonesia’s snack industry. To strengthen its brand appeal, Chiki launched anostalgic edition of Chiki Balls in collaboration with the film “Rangga & Cinta: The Rebirthof Ada Apa Dengan Cinta?”. This strategy employed nostalgic appeals and collective memoryto evoke consumers’ past memories. Although nostalgic appeals and collective nostalgia aretheoretically associated with higher purchase intention, empirical evidence in the Indonesiansnack industry remains limited. This study aims to examine the effect of these two variables onpurchase intention toward the Chiki Balls x Rangga & Cinta nostalgic collaboration product.This study employs a quantitative approach with the Theory of Planned Behavior as itstheoretical foundation. Data were collected from 155 respondents selected through purposivesampling and analyzed using multiple linear regression analysis. The finding show thatperceived attractiveness of nostalgic appeals and perceived collective nostalgia have a positiveand significant effect on purchase intention, with a significance value of 0.000 < 0.05.